Oscillation criteria for Generalized Half Linear Second Order Differential Equations with neutral (Latakia University Journal -Basic Sciences Series, 2019)
We aim in this work to study the oscillation of the second order generalized half-linear neutral differential equation      where , by setting conditions on the coefficients  and  and the function  and .